Peer-to-Peer Lending in Surabaya: How It Drives Regional Economy? - Mahardhika, Galih Satria; Inggis, Raka Achmad (Journal of Developing Economies, 2017)
Financial technology, or so called as "Fintech”, has been remarked as a disruptive idea that changed our current financial system. In Indonesia, one of the emerging financial practices related to Fintech is the online-based peer-to-peer lending (P2PL). This research has two objectives: to explore current scheme of P2PL in Surabaya and to learn how P2PL drives the economy of Surabaya. To meet the objectives, numbers of existing papers are being reviewed related to the matter of P2PL and Micro, Small and Medium Enterprises (MSMEs). Primary data is also gathered through in-depth interview from two basic stakeholders of P2PL in Surabaya: the provider of fintech apps and the owner of MSMEs who is benefiting from the fintech apps. The fintech provider is interviewed regarding to the channeling scheme of funds from the lenders to the MSMEs, while the MSME is interviewed related to the escalation of their business after receiving funds from the P2PL provider. By exploring this topic, the scheme of P2PL and the importance of P2PL to drive regional economy are being clearly described. The results indicate that the funding from P2PL providers help the MSMEs to boost their business performance, and the boosted MSMEs are affecting the regional economy. Keywords: Fintech, Peer-To-Peer Lending, MSMEs, Lending Scheme.JEL: F65, O14, P42